Evaluation of endometrial carcinoma on magnetic resonance imaging. Issue 1 (1st January 2007) - Rockall, A. G.; Meroni, R.; Sohaib, S. A.; Reynolds, K.; Alexander-Sefre, F.; Shepherd, J. H.; Jacobs, I.; Reznek, R. H.
Abstract : Our aims were to assess diagnostic performance of T2-weighted (T2W) and dynamic gadolinium-enhanced T1-weighted (T1W) magnetic resonance imaging (MRI) in the preoperative assessment of myometrial and cervical invasion by endometrial carcinoma and to identify imaging features that predict nodal metastases. Two radiologists retrospectively reviewed MR images of 96 patients with endometrial carcinoma. Tumor size, depth of myometrial and cervical invasion, and nodal enlargement were recorded and then correlated with histology. The sensitivity, specificity, positive and negative predictive values (PPV and NPV) for the identification of any myometrial invasion (superficial or deep) were 0.94, 0.50, 0.93, 0.55 on T2W and 0.92, 0.50, 0.92, 0.50 on dynamic T1W, and for deep myometrial invasion were 0.84, 0.78, 0.65, 0.91 on T2W and 0.72, 0.88, 0.72, 0.88 on dynamic T1W. The sensitivity, specificity, PPV and NPV for any cervical invasion (endocervical or stromal) were 0.65, 0.87, 0.57, 0.90 on T2W and 0.50, 0.90, 0.46, 0.92 on dynamic T1W, and for cervical stromal involvement were 0.69, 0.95, 0.69, 0.95 on T2W and 0.50, 0.96, 0.57, 0.95 on dynamic T1W. Leiomyoma or adenomyosis were seen in 73% of misdiagnosed cases. Sensitivity and specificity for the detection of nodal metastases was 66% and 73%, respectively. Fifty percent of patients with cervical invasion on MRI had nodal metastases. In conclusion, MRI has a high sensitivity for detecting myometrial invasion and a high NPV for deep invasion. MRI has a high specificity and NPV for detecting cervical invasion. Dynamic enhancement did not improve diagnostic performance. MRI may allow accurate categorization of cases into low- or high-risk groups ensuring suitable extent of surgery and adjuvant therapy